Analisis Kepuasan Siswa Terhadap Penggunaan Google Classroom Di Jurusan DKV SMKN 1 Kamal - Alfina Kusuma Nilasari; Prita Dellia; Mutmainnah Mutmainnah; Tria Wulandari; Jantopal Jantopal (Departement of Mathematics Education, 2024)
One innovation in the field of education is the development of learning media. Google Classroom offers various conveniences for teaching and learning both online and offline. Google Classroom provides various features in the application, users can assign assignments, carry out assessments, publish information, and save learning archives. With a total of 54 respondents, the aim of this research was to find out how satisfied students were with using Google Classroom in the DKV department at SMKN 1 Kamal. The research methodology used is the PIECES framework which includes Performance, Information and Data, Economics, Control and Security, Efficiency and Service. The results of this research achieved an average score for each domain, namely the performance domain obtained a result of 4.027 (satisfied), the Information and Data field achieved a result of 3.976 (satisfied), the Economics domain obtained a result of 3.796 (satisfied) the Control and Security domain obtained a result of 3.824 (satisfied), the Efficiency domain obtained a score of 3.879 (satisfied), and the Service domain obtained a score of 3.888 (satisfied). The result of the total average level of satisfaction with using the classroom for all domains is 3.898 (satisfied).